PENGARUH PEMBELAJARAN AQIDAH AKHLAK TERHADAP MORAL KEAGAMAAN PESERTA DIDIK KELAS lV MADRASAH IBTIDAIYAH NEGERI 1 GOWA - Rizki Afdilah, Ulfah; Samsuriadi; Ainun Jariah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Ibtidaiyah Negeri 1 Gowa, who were also used as the research sample, totaling 26 students. The research instrument used was a questionnaire distributed to students to analyze the effect of Aqidah Akhlak learning on their religious morals. Data analysis was conducted using descriptive and inferential statistics with the assistance of SPSS version 25. The results of descriptive analysis indicated that Aqidah Akhlak learning was in the very good category at 69.23% and the good category at 30.77%. Meanwhile, students’ religious morals were in the very good category at 80.77% and the good category at 19.23%. The normality test showed that the data were normally distributed with a significance value of 0.200 > 0.05. Furthermore, hypothesis testing using the Product Moment correlation showed that r-count = 0.402 > r-table = 0.388 at a significance level of 5%, indicating that H0 was rejected and Ha was accepted. This result shows that there is a positive and significant relationship between Aqidah Akhlak learning and the religious morals of fourth-grade students at Madrasah Ibtidaiyah Negeri 1 Gowa.